ISOLASI DAN SELEKSI BAKTERI ASAM LAKTAT DARI YOGHURT KEMASAN YANG BERSIFAT ANTIBAKTERI TERHADAP Escherichia coli DAN Salmonella typhi - Ike Yuliana; Rodesia M. Roza; Atria Martina (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Yoghurt is a fermented product of a group of lactic acid bacteria (LAB) on milk that hasbeen pasteurized. LAB is a group of bacteria that are able to convert carbohydrates(glucose) into lactic acid. LAB produces metabolites that inhibit the growth ofpathogenic bacteria. This study aimed to isolate LAB from yoghurt packaging with itsinhibitory against bacterial pathogens Escherichia coli and Salmonella typhi. LAB wasisolated from 9 samples with 3 brand products and 3 different flavors. Calculation of thetotal population to the overall LAB samples was obtained between 6.4 × 10 6 cfu/ml to2.1 × 10 7 cfu/ml. In this study, inhibition test of pathogenic bacteria E. coli and S. typhiused samples yoghurt. The method used is the well-agar diffusion. The most effectiveyoghurt in inhibiting E. coli was yogurt Ab with diameter of inhibiting zone 23.55 mm,while the yogurt sample that had the highest inhibitory zone which is 19.93 mm forS.typhi was yoghurt Ap.